Bed net use among school-aged children after a universal bed net campaign in Malawi. (December 2016) - Buchwald, Andrea; Walldorf, Jenny; Cohee, Lauren; Coalson, Jenna; Chimbiya, Nelson; Bauleni, Andy; Nkanaunena, Kondwani; Ngwira, Andrew; Kapito-Tembo, Atupele; Mathanga, Don; Taylor, Terrie; Laufer, Miriam
Abstract Background Recent data from Malawi suggest that school-aged children (SAC), aged 5–15 years, have the highest prevalence ofPlasmodium falciparum infection among all age groups. They are the least likely group to utilize insecticide-treated nets (ITNs), the most commonly available intervention to prevent malaria in Africa. This study examined the effects of a universal ITN distribution campaign, and their durability over time in SAC in Malawi. This study identified factors that influence net usage among SAC and how these factors changed over time. Methods Cross-sectional surveys using cluster random sampling were conducted at the end of each rainy and dry season in southern Malawi from 2012 to 2014; six surveys were done in total. Mass net distribution occurred between the first and second surveys. Data were collected on household and individual net usage as well as demographic information. Statistical analyses used generalized linear mixed models to account for clustering at the household and neighbourhood level. Results There were 7347 observations from SAC and 14, 785 from young children and adults. SAC used nets significantly less frequently than the rest of the population (odds ratio (OR) from 0.14 to 0.38). The most important predictors of net usage among SAC were a lower ratio of people to nets in a household and higher proportion of nets that were hanging at the time of survey. Older SAC (11–15 years) were significantly less likely to use nets than younger SAC (5–10 years) [OR = 0.24 (95 % CI: 0.21, 0.28)]. The universal bed net campaign led to a statistically significant population-wide increase in net use, however net use returned to near baseline within 3 years. Conclusions This study suggests that a single universal net distribution campaign, in combination with routine distribution through health clinics is not sufficient to cause a sustained increase in net usage among SAC. Novel approaches to ITN distribution, such as school-based distribution, may be needed to address the high prevalence of infection in SAC.